BAHASA INGGRIS: KURIKULUM 2013: PERBANDINGAN PENERAPAN DI SMP KOTA MADIUN - Lusia Kristiasih Dwi Purnomosasi; Titis Agunging Tyas (Jurnal Penelitian LPPM (Lembaga Penelitian dan Pengabdian kepada Masyarakat) IKIP PGRI MADIUN, 2014)
English in K13 insists on the teachers to be cerative. In fact. It indicates bstacles in the class due to the interpretation on its implementation. The research is a qualitative evaluative one that the researchers are the observers to two schools as the object. It is intended to see the comparison of English subject implementation on K13 focused on the integration within its practices. It also sees how and why they differ from one to another. The analyses show that (1) there are no integration done by teachers on the language skills at class in two schools. (2) The situation and condition of the school influences the practices of teaching English by integration; in one school, classes have good facilities, another school has no one. (3) English in K13 is fun for students because they use to for both schools.  (4) Teachers find difficulties in two schools especially for the assessments, asking phase in scientific approach, and composing worksheets. (5) K13 basically changes from boring to enjoyment because it implies creativity and being active for both teachers and students.